Memory training in older adults with mild cognitive impairment: Positive effects are found five years after MEMO training compared to control intervention. (31st December 2021) - Belleville, Sylvie; Cuesta, Marc; Bier, Nathalie; Brodeur, Catherine; Gauthier, Serge; Gilbert, Brigitte; Grenier, Sébastien; Ouellet, Marie‐Christine; Viscogliosi, Chantal; Hudon, Carol
Abstract: Background: Cognitive training was found to have a positive effect on the memory of healthy older adults, including long‐term benefits (Rebok et al, 2014). This finding offers hope that cognitive training could contribute to prevention approaches. However, little is known regarding the long‐term benefits of cognitive training in older adults with mild cognitive impairment (MCI), many of whom are in the early phase of Alzheimer's disease. In a prior randomized controlled trial (Belleville et al, 2018), we reported a short‐term benefit of cognitive training on the delayed recall of older adults with MCI. The objective of this study was to assess the impact five years later. Method: This is the five‐year follow‐up of a single‐blind randomized controlled trial (MEMO+). Participants with amnestic MCI were randomized to memory training or an active (psychosocial intervention) or passive (no‐contact) control condition. Interventions were provided in small groups over eight two‐hour sessions with a single booster session offered three months following training. In the initial study, participants were assessed post‐training, as well as three and six months after the intervention. The 127 participants with MCI, who completed the 6‐month post‐training assessment, were contacted five years post‐training. Primary outcomes included a 12‐word free recall task, a self‐reported strategy used in everyday life, and the Montreal Cognitive Assessment screening test (MoCA). Participants randomized to cognitive training were compared to those randomized to the control conditions. Result: Participants with MCI, who were randomized to the cognitive training condition, showed a reduced 5‐year decline on the delayed recall task when compared to participants in the control conditions. Participants randomized to the cognitive training condition also demonstrated superior delayed recall and MoCA performance than those in the control condition, five years post‐training. There were no differences on self‐reported strategy use. Conclusion: The positive effect of cognitive training was found five years later on measures of delayed memory and global cognitive status in individuals with MCI. This indicates that the use of cognitive training is a valid preventive approach and has potential to delay the onset of dementia in at‐risk individuals.